2020
DOI: 10.1002/mgg3.1130
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequencing analysis of a family with a child displaying severe abdominal distention and recurrent hypoglycemia

Abstract: Background Germline mutations in PTEN are associated with the PTEN hamartoma tumor syndrome (PHTS), an umbrella term used to describe a spectrum of autosomal‐dominant disorders characterized by variable phenotypic manifestations associated with cell or tissue overgrowth. We report a boy who developed severe progressive abdominal distention due to a dramatic adipose mass from the age of 7 months and developed recurrent hypoinsulinemic hypoglycemia that led to seizures at the age of 4 years. Methods Trio‐based w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Further publications pointed out that hypoglycemia with a similar biochemical profile may also occur in a subset of patients with other PI3K-AKT pathway disorders caused by (mosaic) activating mutations in AKT3, PIK3CA, PIK3R2, and CCND2, thus suggesting that this type of metabolic dysregulation is in principle shared by the entire group of disorders (43, 44). Consistent with this, Saito et al described a case of AKT1-caused Proteus syndrome with hypoinsulinemic hypoglycemia (45), and Liu et al reported a case with PTEN-related overgrowth (OMIM #158350) and recurrent hypoketotic hypoglycemia (46). Onset of hypoglycemia in patients with PI3K-AKT pathway disorders was variable, mostly within the first years of life but not typically neonatal.…”
Section: Pi3k-akt Pathway Disordersmentioning
confidence: 76%
See 1 more Smart Citation
“…Further publications pointed out that hypoglycemia with a similar biochemical profile may also occur in a subset of patients with other PI3K-AKT pathway disorders caused by (mosaic) activating mutations in AKT3, PIK3CA, PIK3R2, and CCND2, thus suggesting that this type of metabolic dysregulation is in principle shared by the entire group of disorders (43, 44). Consistent with this, Saito et al described a case of AKT1-caused Proteus syndrome with hypoinsulinemic hypoglycemia (45), and Liu et al reported a case with PTEN-related overgrowth (OMIM #158350) and recurrent hypoketotic hypoglycemia (46). Onset of hypoglycemia in patients with PI3K-AKT pathway disorders was variable, mostly within the first years of life but not typically neonatal.…”
Section: Pi3k-akt Pathway Disordersmentioning
confidence: 76%
“…described a case of AKT1-caused Proteus syndrome with hypoinsulinemic hypoglycemia ( 45 ), and Liu et al. reported a case with PTEN-related overgrowth (OMIM #158350) and recurrent hypoketotic hypoglycemia ( 46 ). Onset of hypoglycemia in patients with PI3K-AKT pathway disorders was variable, mostly within the first years of life but not typically neonatal.…”
Section: Resultsmentioning
confidence: 99%
“…84 Liu et al identified a PTEN germline variant (c.849 delA, P.Lu284argfs) in genetic testing in a child with no typical phenotype, which was clinically manifested as a persistently enlarged abdominal tumor with high fat content and repeated episodes of hypoglycemia. 85…”
Section: Juvenile Polyposis Syndromementioning
confidence: 99%